Evaluación del rendimiento en la fase de crecimiento del cultivo de sábila (Aloe vera barbadensis Miller) utilizando tres tipos de fertilizantes, a dos frecuencias de aplicación. - Granda Barahona, Oscar Froilán (2017)
VIII. SUMMARY This research aims to evaluate the performance in the growth phase of the culture of aloe (Aloe vera barbadensis,M) using three types of fertilizers, two frequencies of application, located in the San Genaro, community San Francisco, parish Selva cheerful, canton Otavalo, Imbabura province, located at the geographic coordinates 00º 22 '59' 'north latitude, 78 ° 60' 23 '' west longitude at an altitude of 1,336 meters above sea level, this work was performed in order to determine the type optimal for crop yield aloe vera fertilization, evaluate the most appropriate frequency in the application of fertilizers to optimize this category in the production of Aloe Vera and economically analyze treatments to identify suitable areas for the production of Aloe Vera. Seven treatments by the combination of three types of fertilization, two frequencies of application and a control without application was investigated. Design Randomized Complete Block (DBCA) was used factorial arrangement A x B + 1 with 7 treatments and three repetitions, giving a total of 21 experimental units. The total area of the experiment was 568.48 m2, 15,68 m2 plots with a useful area of 4,90 m2. It was evaluated, plant height, number of leaves, along basal leaves, leaf width measured at the base sheet, thickness of the basal leaves, measured on the basis of the sheet number of commercial sheets, weight commercial sheets, efficiency of fertilizers and organic fertilizers and percentage of effectiveness of fertilizers and organic fertilizers. Checking measures of treatments was performed using test Duncan Multiple Range 5% probability. The results determined that the cultivation of aloe variety Aloe Vera Barbadensis Milller, responded favorably to the application of rates of fertilization and frequency of application, the types of chemistry, organic and chemical + organic fertilization showed favorable results compared to the control treatment without application, the greater the length and breadth of commercial basal leaves is obtained with the frequency of bi-monthly application and greater agronomic yield per unit area the gets treatments, Organic - monthly and Chemistry + Organic - monthly and Chemistry - bimonthly which earned the highest net profit.